APPLICATION OF INTERNET OF THINGS (IOT) TECHNOLOGY IN PROTOTYPES OF BUILDING-FIRE DISASTER MITIGATION SYSTEMS - Iqbal Mauludi (Ben Gurion), M
Building and residential fires frequently occur in Indonesia, and their numbers continue to rise. Along with preventing the causes of building and residential fires, a proper mitigation system is necessary. Mitigation is the process of attempting to reduce the effects of a disaster. This thesis aims to develop a prototype of a building-fire mitigation system using IoT technologies and focused on forecasting the fastest and the safest evacuation path. The Dijkstra algorithm has been used to forecast this evacuation route. Temperature data is acquired from the thermistor temperature sensor and then transmitted to the Raspberry Pi 3B using the Message Queuing Telemetry Transport (MQTT) protocol via NodeMCU v3. Calculation and modeling of the expected evacuation path has been performed using Node-Red on the Raspberry Pi 3B. Meanwhile, the modeling results has been displayed on the Node-Red Dashboard's network page. The fastest and the safest evacuation path is predicted based on the results of experiments and simulations. It demonstrates that the prototype of the proposed building-fire mitigation system is feasible to be implemented in larger scale.